Lizzie Bright and the Buckminster boy - Schmidt, Gary D. (New York Laurel-Leaf, 2004)
In 1911, Turner Buckminster hates his new home of Phippsburg, Maine, but things improve when he meets Lizzie Bright Griffin, a girl from a poor, nearby island community founded by former slaves that the town fathers--and Turner's--want to change into a tourist spot.
Keywords: Progress -- Fiction; Race relations -- Fiction; Moving, Household -- Fiction; Clergy -- Fiction; Maine -- History -- 20th century -- Fiction